The influence of communication skill toward employee performance in radiology installation unit of hospital - Soekardi, Adi; Indrawati, Ratna; Erni, Nofi (Management and Entrepreneurship: Trends of Development, 2020)
Staff performance is the result in quality and quantity that an employee can achieve in carrying out tasks related to the assigned responsibilities. Effective communication will help to create a healthy and open performance. This is very important in order to increase creativity and dedication of employees or staff at hospital. This research aims to analyze significant influence of leadership style and communication skills on staff performance by job satisfaction as intervening variable. Research method used here is quantitative research method method with causality research. The data source consists of primary data. The subjects of analysis were the employees in emergency radiology and diagnostic radiology. Data analysis was done byAMOS-path analysis. The results of the study showed that leadership style, communication skills and job satisfaction have a positive and significant effect on staff performance. Partially, there is a significant influence between communications on performance. The research findings show that leadership and communication styles may have a large direct influence on staff performance without influenced by job satisfaction. Leadership style has a negative influence on job satisfaction compared to staff performance. Communication skills have the greatest impact on improving staff performance compared to leadership styles and job satisfaction.JEL Classification: A130, M540, M520